2016
DOI: 10.1093/mnras/stw191
|View full text |Cite
|
Sign up to set email alerts
|

The frequency of snowline-region planets from four years of OGLE–MOA–Wise second-generation microlensing

Abstract: We present a statistical analysis of the first four seasons from a "second-generation" microlensing survey for extrasolar planets, consisting of near-continuous time coverage of 8 deg 2 of the Galactic bulge by the OGLE, MOA, and Wise microlensing surveys. During this period, 224 microlensing events were observed by all three groups. Over 12% of the events showed a deviation from single-lens microlensing, and for ∼1/3 of those the anomaly is likely caused by a planetary companion. For each of the 224 events we… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

10
124
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
5
4

Relationship

4
5

Authors

Journals

citations
Cited by 130 publications
(135 citation statements)
references
References 42 publications
10
124
1
Order By: Relevance
“…63 The minimum in this distribution can then be regarded as the location of the mean boundary between two formation mechanisms averaged over the microlensing host-mass distribution. Shvartzvald et al (2016) found that this minimum was near q∼0.01, which corresponds to M comp ∼5 M Jup for characteristic microlensing hosts, which are typically in the M dwarf regime. This tends to indicate that this boundary scales as a function of the host mass.…”
Section: Planets At the Desert's Edgementioning
confidence: 92%
See 1 more Smart Citation
“…63 The minimum in this distribution can then be regarded as the location of the mean boundary between two formation mechanisms averaged over the microlensing host-mass distribution. Shvartzvald et al (2016) found that this minimum was near q∼0.01, which corresponds to M comp ∼5 M Jup for characteristic microlensing hosts, which are typically in the M dwarf regime. This tends to indicate that this boundary scales as a function of the host mass.…”
Section: Planets At the Desert's Edgementioning
confidence: 92%
“…This then sets the stage for whether its parallax is "adequately measured" according to the Zhu et al (2017b) criteria, or rather whether the corresponding 63 As a result, in microlensing statistical studies, the planet/brown-dwarf boundary is often defined by q. For example, Suzuki et al (2016;following Bond et al 2004) and Shvartzvald et al (2016) use q=0.03 and q=0.04, respectively, which would correspond to the conventional 13 M jup limit for stars of mass M;0.4 M e and M;0.3 M e , respectively. point-lens event would have satisfied them.…”
Section: Construction Of Blind Tests In the Facementioning
confidence: 99%
“…Clanton & Gaudi (2014) found that the planet abundances estimated by microlensing are consistent with those found by radial velocity. Recently, Shvartzvald et al (2015) estimated planet abundance and mass function based on nine events and found that 55% of stars host a planet beyond the snow line and Neptune-mass planets are ∼10 times more common than Jupiter-mass planets. Suzuki et al (2016) found a break and possible peak in the exoplanet mass ratio function at~-q 10 4 and found 0.75 planets per star at >´-q 5 10 5 and 1.12 planets per star for > q 0.…”
Section: Introductionmentioning
confidence: 99%
“…This is in contrast to estimates through other techniques, such as radial velocity and transit, which find that BDs are rare (<1%, Grether & Lineweaver 2006) at closer separations. A possible explanation for this difference besides the different separations, as suggested by Shvartzvald et al (2016), is that different host stars are mostly probed by each technique-FGK stars by radial velocity and transits versus M stars by microlensing.…”
Section: Discussionmentioning
confidence: 99%